EFFECT OF CHELATED IRON AND GA3 SPRAY ON THE GROWTH OF OLIVE TRANSPLANTS Olea eurotaea L. - Jassim Al-Aareji; Muna Sharif (Mesopotamia Journal of Agriculture)
Transplants of three cultivars of Olive (Khodeiri, Dremalali and Sorani),were sprayed with four levels of chelated iron (0, 10, 20 and 30 mg Fe/L.), and four levels of GA3 (0, 50, 100, and 150 mg GA3/L.) three times /season . The time period between one spray and anther was one month .The results obtained in the mid of October 2001 indicated that the sprayed cultivars transplant with iron at the concentration of 30mg.Fe/L.and GA3 at the concentration of 150mg. GA3/L. alone or both leads to a significant increase in the amount of chlorophyll A and B, number and length of branches, dry weight of leaves, stem and branches and roots.